Swim starts performances at the turkish national championships - Gumus, M.; Akalin, T. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The start in swimming, together with the other elements of the race, is very important for achieving better results in championships. Start times were shown to consist of between 0.8% and 26.1% of the overall race time depending on the event. Getting a good (lucky)-start, or psyching your opponents out of a quick-start, can make all the difference it takes to get a world record or Olympic medal. The purpose of our study was to evaluate of starting reaction time of Turkish swimmers participated to 2011 Turkish National Championships. Methods: In this study, 1738 official competition times of 313 swimmers (157 female, 156 male) who participated in 2011 Turkish National Championships. Competition was performed in 50 m indoor swimming pool by permission of Turkish Swimming Federation and the data of starting reaction time -the duration between the starting signal and when the feet leave the block- measurements were obtained by SWISS TIMING (OMEGA) that is official partner of FINA. Data were evaluated by using SPSS for Windows 16.0 software and mean values were represented as "arithmetic mean±standard deviation". ANOVA test, student t test, posthoc bonferroni test and pearson corelation analysis were used for the comparisons between the measurements. Results of analysis were evaluated with 95% confidence interval. Results: Participation in the competition all the swimmers an average starting reaction time (SRT) was 0.78±0.09s. SRT was 0.80±0.9s for female, 0.76±0.08s for male and there was a significant difference between groups (p=0.001). SRT was 0.80±0.09s for youth, 0.77±0.09s for junior, 0.76±0.07s for senior and there was a negative and significantly correlation between SRT and age groups (r=0.217, p=0.001). There was a positive and significantly correlation between SRT and race distance (short distance: 0,76±0,08, long distance; 0,81±0,09) (r=0.186, p=0.001). In championship, there was a significantly difference between semi-final categories by SRT (p=0.001) and SRT was 0.79±0.09s for elimination races, 0.77±0.09s for semi-finals and 0.79±0.09s for finals. There was a positive and significantly correlation between SRT and rankings, the first three best placed athletes 0,76±0,09 and the others 0,78±0,09s. Discussion: In the men`s 50 m freestyle final in the Sydney Olympic Games, there was only 0.05s separating 1st and 3rd places and in the same event at the 2003 World Championships, 0.52s separated 1st and 8th place. In 50 and 100 m swimming races, performance has been strongly linked to start performance. These values are laid down on the Turkish population in the coming years, and the races are very important in order to allow comparison.